Pan African Feminist Perspectives Promoting Matriarchy. Women’s Pre-Colonial Linguistic Power Perspectives, Power Loss and the Contemporary State of Affairs in Ankole Sub-Region - Asiimire, Donath; Twinamatsiko, Medard (Open Access Library Journal, 2021)
This paper studies the linguistic approach used to describe wise, healer and powerful women in the Ankole Sub-region during the pre-colonial times. Discussed in the study are the names, words and proverbs that describe a general perspective of women and illustrate how women were powerful before colonialism. The paper also presents how women were later oppressed and lost power during the colonial period. Finally, the paper puts forwards ways of reclaiming women’s power in the Ankole Sub-region.
Keywords: Women and Economic Power; Women and Political Power; Women and Social Power